Influence of Work Discipline, Work Motivation and Workload on Employee Productivity - Desita, Wanda; Ismartaya; Yulianingsih (MultiTech Publisher, 2024)
This research aims to investigate how work discipline, work motivation, workload, and productivity are interrelated, laying groundwork for future studies. Multiple linear regression analysis is the chosen method, with a sample size of 100 individuals. Results show that work discipline, motivation, and workload collectively influence employee productivity, highlighting their importance in enhancing performance.